Beetroot (Beta vulgaris L. var. rubra L.) flour proportion and oven temperature affect the physicochemical characteristics of beetroot cookies. Issue 1 (April 2020) - Aulia, F; Sunarharum, W B
Abstract: Red beetroot ( Beta vulgaris L. var. rubra L.) is one of the agricultural commodities that is very beneficial for human health, one of the benefits is to facilitate the transport of nutrients throughout the body and maintain the number of red blood cells. However, the utilization of red beetroot commodities is still limited, especially in Indonesia. For this reason, innovation is required in the manufacture of red beetroot derivative products. This study aims to know the effect of beetroot flour proportion and oven temperature on the physicochemical characteristics of beetroot cookies. This study was conducted by using Factorial Randomized Block Design consisting of two treatment factors, i.e. proportion of beet flour (10%, 15%, and 20%) and oven temperature (160°C, 170°C, and 180°C) in three replicates. Statistical analysis was performed using Minitab 17. Best treatment was selected by Multiple Attribute method. The results showed that the factor of increasing the proportion of beetroot powder and oven temperature had a significant effect on lightness, redness, yellowness, hardness, fracturability, moisture content, and crude fiber of the cookies. The interaction between the two factors of beetroot powder proportion and oven temperature was significantly (α=0.05) affecting the brightness, redness, and yellowness, and crude fiber, but did not significantly affect hardness, fracturability, and moisture content. Best treatment was the cookies made of 15% proportion of beetroot and 180°C of oven temperature that contains potassium of 476.16 mg / kg, magnesium of 2045.76 mg / kg, and phosphorus (P) of 2801.6 mg / kg.